What Goes Around Comes Around: The Circulation of Proverbs in Contemporary Life - Tokofsky, Peter (Utah State University, University Libraries, 2004)
In this collection of essays, prominent folklorists look at varied modern uses and contexts of proverbs and proverbial speech, some traditional and conventional, others new and unexpected. After the editors' introduction discussing the history and status of attempts to define proverbs, describing their contemporary circulation, and acknowledging the especially important work of paremiologist Wolfgang Meider, the contributions examine the continuing pervasiveness and idiomatic relevance of proverbs in modern culture.